LABORATORY BLOOD MARKERS DYNAMICS IN PATIENTS WITH GONARTHROSIS AND KNEE JOINT CONTRACTURE BEFORE AND AFTER TOTAL KNEE REPLACEMENT AND THEIR FURTHER REHABILITATION - Arutyunyan, Z.A.; Morozenko, D.V.; Tulyakov, V.O. (World of Medicine and Biology, 2020)
The article is devoted to the change of blood laboratory indexes in patients with knee osteoarthritis with knee contractures before and after total knee replacement with further rehabilitation. In patients with knee osteoarthritis stage IV, 2 months after knee replacement without development of flexed contracture of knee a decline of activity of inflammatory-destructive processes was observed in bone and cartilaginous tissues, registered on the reliable decreasing of maintenance of glycoproteins, chondroitinsulphates, activity of alkaline phosphatase in blood serum and ESR of patients testifies to efficiency of knee replacement. Patients with knee osteoarthritis IV stage, 2 months after total replacement with development of flexed contracture of knee was fixed resistant reliable change of maintenance of glycoproteins, chondroitinsulphates, activity of alkaline, acid phosphatases in blood serum and ESR, which are adjective for increasing of activity of inflammatory-destructive processes in an organism of patients, that rehabilitation is required. Rehabilitation 14 days after Knee replacement improved the clinical state of patients and diminished activity of inflammatory-destructive processes in an organism, what was reflected partial normalization of researched parameters.
Keywords: knee osteoarthritis; replacement; biochemistry; dynamics; rehabilitation